Pathology of cattle experimentally intoxicated with ground Ricinus communis seeds - Marin, Raul Eduardo (2018)
Five Aberdeen Angus calves were inoculated intra-ruminally with ground seeds of Ricinus communis at doses of 1, 1.5, 2 or 3 gr per kg of body weight, or with saline solution (control), respectively. Grossly, all intoxicated animals showed hemorrhages in abdominal serosas, epicardium, endocardium, spleen, pre-stomachs, abomasum, and small and large intestine, and diffuse edema of the ruminal mucosa. Microscopically, in all animals inoculated with R. communis seeds, the main feature was the presence of pyknotic and karyorrhectic nuclei in the endothelium of central nervous system, hepatic, ruminal, intestinal, glomerular and alveolar capillaries, and in lymphoid cells of multiple organs. Apoptosis, confirmed by activated caspase-3 immunohistochemistry, was observed in these cells. No gross or microscopic lesions were observed in the control animal. The results of this study suggest that apoptosis is the main mechanism of cell death in cattle intoxicated with R. communis seeds.